2005
DOI: 10.1007/s10519-005-6189-1
|View full text |Cite
|
Sign up to set email alerts
|

A School-based Twin Study of Handedness among Adolescents in Taiwan

Abstract: This study aimed to evaluate whether twinning might influence handedness and the relative contribution of genetic and environmental factors to handedness in a total of 321 pairs of twins, 36 same-sex sib-pairs, and 1020 singletons, aged 12-16 and systematically recruited from the junior high schools in Taipei. Twins' zygosity was determined by a combination of DNA typing and physical similarity. The direction and consistency of handedness in twins did not differ from that seen in singletons. Compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…While isolated studies (e.g. Warren et al 2006) have reported positive heritabilities for some handedness measures, the overall picture across multiple studies remains that handedness, at least as measured in the vast majority of questionnaire and performance studies, does not exhibit strong heritability (McManus 1985;Neale 1988;Su et al 2005).…”
Section: Case Studies Of Gene-culture Coevolutionmentioning
confidence: 99%
“…While isolated studies (e.g. Warren et al 2006) have reported positive heritabilities for some handedness measures, the overall picture across multiple studies remains that handedness, at least as measured in the vast majority of questionnaire and performance studies, does not exhibit strong heritability (McManus 1985;Neale 1988;Su et al 2005).…”
Section: Case Studies Of Gene-culture Coevolutionmentioning
confidence: 99%
“…The sampling of the participants has been described in detail elsewhere (Kuo et al 2004;Su et al 2005). In brief, a list of twins was solicited from the 71 junior high schools in Taipei City.…”
Section: Participantsmentioning
confidence: 99%
“…This study (Su et al, 2005) aimed to evaluate whether twinning influences handedness and the relative contribution of genetic and environmental factors to handedness. In total, we have complete handedness data from 357 twin/sibling pairs , consisting of 233 MZ twin pairs (128 female, 105 male), 46 same-sex DZ twin pairs (24 female, 22 male), 36 same-sex sibling pairs (23 female, 13 male), and 42 OS pairs.…”
Section: Handednessmentioning
confidence: 99%